Advocacy in international commercial arbitration - Elliott Geisinger; Guillaume Tattevin (JurisNet, 2013)
Corporate counsel, arbitrators and lawyers discuss their experiences with advocates in international arbitration, their expectations of good advocacy in a critical analysis of The ASA Charter of Advocacy in International Commercial Arbitration. Issues discussed include: differences in culture and style; evolution of the role model over time; the relationship with the client and the tribunal; the relationship with witnesses and experts; the use of consultants and their management